The Contrasts in Popular Fiction Genre on the Example of The Three Musketeers and The Count of Monte-Cristo by Alexander Dumas - Lesiak, Weronika (Contrasts in humanities: literature, language, culture, 2023)
The aim of this article is to take a closer look at the nature of popular fiction and its inherent usage of contrasting elements. We would like to examine two Alexander Dumas’ novels, The Three Musketeers and The Count of Monte-Cristo in order to try to explain the aforementioned tendency as well as give examples illustrating it. In the first part of the text, we concentrate on premises of the genre in general. Having established those principles, we go on to analyse The Three Musketeers in the context of its contrasting features. We can divide this novel into three basic sets of oppositions: that between the cardinal and the queen, that between titular characters, accompanied by d’Artagnan, and finally that between main female characters, Constance and Milady. After the analysis of the first of the novels, we then proceed to study The Count of Monte-Cristo. We draw attention to its most distinctive contrasts which include, amongst others, the opposition between the protagonist’s two incarnations: Edmond Dantès and the count of Monte-Cristo. All in all, both novels represent well the tendency to use contrasts as a means of characterization. The popular fiction’ structure which presupposes that the good must be victorious and the bad punished fits well with the utilisation of oppositions.